Crust-mantle branch of the global carbon cycle and origin of deep-seated hydrocarbons - Sorokhtin N. O.; Nikiforov S. L.; Kozlov N. E. (Vestnik MGTU, 2018)
The processes of multi-stage and polycyclic transformation and transfer of carbon in the crust and mantle have been described. The sediments drawn in the plate underthrust zones break down, become transformed and altered by metamorphic events, and part of the newly formed carbon compounds is transferred by the mantle convective currents to rift zones of the mid-oceanic ridges and carried up to the surface as hydrocarbons of various composition and carbon dioxide. This material becomes re-deposited on the sea floor as sediments forming carbonaceous and carbon-bearing units. As a result of multi-stage mechanism of physical and chemical transformations in the crust-mantle areas of the Earth hydrocarbon compounds acquire features of abiogenic origin remaining, in fact, exogenic. The revealed crust-mantle carbon cycle represents part of a global process for the cyclic carbon transfer from the atmosphere to the mantle and back. The scale of its manifestation is likely not so wide, and numerous small (mm and portions of millimeters) particles of exogenic substance and dispersed carbon drawn in the plate underthrust zones form a stable geochemical tail of the crustal direction in the mantle propagating in the plane of convective currents motion. The scale of this process may be indirectly suggested by the volumes of hydrocarbon and carbon dioxide de-gassing and hydrogen in the rift systems of the Earth crust. The amount of generated hydrocarbon gases with deep-seated origin cannot form large gas and oil-and-gas fields since their significant part is transferred to the atmosphere. Just some portion of compounds may be deposited in oceanic sediments and generate gas-hydrate pools.